The secret world of the baby - Romulo, Beth Day 1924-; Liley, H. M. I. (New York Random House, 1968)
Focuses on the development of and influences on the unborn child, his reactions to birth, and his life as an independent being.
Keywords: Childbirth -- Juvenile literature; Babies; Childbirth; Infants -- Juvenile literature